Early detection of colonic dysplasia by magnetic resonance molecular imaging with a contrast agent raised against the colon cancer marker MUC5AC. (14th January 2016) - Rossez, Yannick; Burtea, Carmen; Laurent, Sophie; Gosset, Pierre; Léonard, Renaud; Gonzalez, Walter; Ballet, Sébastien; Raynal, Isabelle; Rousseaux, Olivier; Dugué, Timothée; Vander Elst, Luce; Michalski, Jean‐Claude; et al.
Abstract : Human gastric mucin MUC5AC is secreted in the colonic mucus of cancer patients and is a specific marker of precancerous lesions called aberrant crypt foci. Using MUC5AC as a specific marker can improve sensitivity in the detection of early colorectal cancer. Here we demonstrated that the accumulation of MUC5AC in xenograft and mouse stomach can be detected by magnetic resonance imaging (MRI). We used ultrasmall particles of iron oxide (USPIOs) conjugated with disulfide constrained heptapeptide that were identified using a screening phage display. To accomplish this, we employed positive selection of the phage display library on MUC5AC purified from fresh human colonic adenomas in combination with negative selection of the phage library on purified human MUC2, which is predominantly found in normal colorectal tissues. This conjugate was tested on human colorectal cancer cell lines that were either able or unable to secrete MUC5AC, both in vitro and in vivo. MUC5AC–USPIO contrast agent and USPIOs alone were not detected in cell lines unable to secrete MUC5AC. A combination of MRI and microscopy studies was performed to detect a specific accumulation of the contrast agent in vivo . Thus, the MUC5AC contrast agent enabled non‐invasive detection of precancerous lesions and colorectal cancer, highlighting its potential use in diagnostics, in the early detection of colorectal cancer recurrences after treatment and in mechanistic studies implicating MUC5AC. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : After intravenous injection of USPIOs conjugated with a MUC5AC‐specific peptide, negative T 2 weighted contrast in MR images was generated by the specific binding to MUC5AC.